Plasma-sprayed TiO2 coatings: Hydrophobicity enhanced by ZnO additions - Yusuf, Yusliza; Ghazali, Mariyam Jameelah; Mohamad Juoi, Jariah; Abd Rahim, Toibah; Mustafa, Zaleha (John Wiley and Sons Inc, 2022)
Titanium dioxide (TiO2) powder mixed individually with 10 and 30 weight percentage (wt%) ZnO was thermally sprayed onto a grade B API 5 L carbon steel substrate by atmospheric plasma spraying. The effect of the addition of ZnO (10 wt% and 30 wt%) on the microstructures and wettability properties of the TiO2/ZnO coatings was investigated. The characterization of the coatings was carried out using scanning electron microscopy, X-ray diffraction (XRD), laser confocal microscope, and sessile droplet system. The XRD analysis of the coating revealed that the anatase phase of TiO2 in the powder state transformed into rutile phases for the produced TiO2/ZnO coatings. Surface microstructure analysis revealed that the coatings had typical micro-roughened surfaces of plasma spraying products. The coating with 30 wt% ZnO produced a coating with remarkable pores and microcracks compared with the TiO2 coating and coating with 10 wt% ZnO. Additionally, the increase in the wt% of ZnO increased the surface roughness value of the produced coatings and substantially changed the wettability properties of the TiO2 coating from hydrophilic to hydrophobic.